MARKETING STRATEGY THROUGH DIGITALIZATION TO INCREASE INCOME OF POTTERY MSMES IN KLATEN, CENTRAL JAVA - Siti Mulasih; Asep Surya Lesmana (Journal Of Applied Multidisiplinary Studies, 2025)
The development of digital technology has brought significant changes to product marketing patterns, including for Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze marketing strategies through digitalization to increase the revenue of pottery MSMEs in Klaten, Central Java. Digitalization is considered an effective solution for expanding market reach, strengthening product image, and enhancing competitiveness amidst increasingly fierce global competition. The research method used was descriptive qualitative, with a case study approach involving several pottery MSMEs in Klaten. Data was obtained through interviews, observations, and documentation studies related to the implementation of digital marketing strategies, such as the use of social media, marketplaces, and creative content-based promotions. The results show that the implementation of digital marketing strategies has a positive impact on increasing sales and revenue for MSMEs. The use of social media such as Instagram and TikTok plays a crucial role in building brand awareness and attracting consumer interest, while the use of marketplaces helps expand market access beyond the region. However, obstacles remain, including limited digital literacy, a lack of ability to create engaging content, and minimal technological support. Therefore, ongoing training and mentoring from local governments and educational institutions are needed to improve the digital competency of MSMEs. Overall, digital marketing strategies have proven effective in increasing the revenue of pottery MSMEs in Klaten and have the potential to become a model for developing a creative economy based on local wisdom in the digital era.